What happens when nothing happens? An investigation of pauses as a compensatory mechanism in early Alzheimer's disease. (18th February 2019) - Pistono, A.; Pariente, J.; Bézy, C.; Lemesle, B.; Le Men, J.; Jucla, M.
Abstract: Lexical-semantic impairment is one of the earliest symptoms of Alzheimer's disease (AD) and is usually examined by single word processing tasks. During speech production, pauses are often investigated as a hallmark of a patient's lexical-semantic decline. In the current study, we put forward the hypothesis that pauses reflect different processes according to the type of discourse. We believe that lexical and semantic impairment would predict a patient's pause frequency in a picture-based narrative (PBN) while anterograde memory would predict a patient's pause frequency in a memory-based narrative (MBN). To demonstrate this, we recruited 17 early AD patients and 17 matched controls. They underwent a full neuropsychological and language assessment and two narrative production assessments. We compared pause duration and frequency in the AD participants' and healthy controls' PBN and MBN. A multiple regression model was used in each narrative and in each group individually to assess the relationship between cognitive processes and pause frequency. Our results show that participants with AD produced more pauses in the PBN only. The frequency was predicted by semantic fluency performance with which it was positively correlated, contrary to what was expected. In the MBN, pause frequency in the AD participants was positively correlated with and predicted by their memory performance. We then examined the neuroanatomical correlates of pause frequency in the AD participants. Considering the PBN, pause frequency was also positively correlated with the grey matter density of the anterior temporal lobe. These findings suggest that patients use pauses as compensatory mechanisms in the earliest stages of AD. Pauses therefore may reflect the time required for the compensation and the realisation of a weak process depending on the narrative task and should be considered as a positive sign. Highlights: Early AD patients use pauses differently according to the narrative type. The frequency of pauses reflects different processes according to the narrative. Patients use pauses as compensatory mechanisms in the earliest stages of AD.